Effect of vitamin B12 and folic acid supplementation on biomarkers of endothelial function and inflammation among elderly individuals with hyperhomocysteinemia. (April 2016) - van Dijk, Suzanne C; Enneman, Anke W; Swart, Karin MA; van Wijngaarden, Janneke P; Ham, Annelies C; de Jonge, R; Blom, Henk J; Feskens, Edith J; Geleijnse, Johanna Marianne; van Schoor, Natasja M; Dhonukshe-Rutten, Rosalie AM; de Jongh, Renate T; et al.
B-vitamin trials failed to demonstrate beneficial effects on cardiovascular outcomes, but hyperhomocysteinemia still stands out as an independent cardiovascular risk factor, particularly in elderly individuals. B-vitamins may influence early vascular dysfunction, such as endothelial dysfunction, or may have adverse effects, for example on inflammation. We investigated the effect of B-vitamins on endothelial function and inflammation within an interventional study. This study was conducted within the framework of the B-PROOF trial, which included 2919 hyperhomocysteinemic elderly individuals, who received daily vitamin B12 (500 μg) and folic acid (400 μg) or placebo for 2 years. Using an electrochemiluminescence platform, we measured intercellular adhesion molecule 1 (ICAM-1), vascular adhesion molecule 1 (VCAM-1), serum amyloid A (SAA), vascular endothelial growth factor (VEGF) and C-reactive protein (CRP) at baseline and follow-up in a subsample of 522 participants (271 intervention group; 251 placebo). Treatment effects were analyzed with ANCOVA. The participants had a mean age of 72 years, and 55% of them were male. At the 2-year follow-up, B-vitamins did not change the ICAM-1 (+36% change in the intervention group versus +32% change in the placebo group; p = 0.72), VCAM-1 (+27% vs +25%; p = 0.39), VEGF (–1% vs +4%; p = 0.40), SAA (+34% vs +38%; p = 0.85) or CRP levels (+26% vs +36%; p = 0.70) as compared to placebo. In conclusion, in elderly patients with hyperhomocysteinemia, vitamin B12 and folic acid are unlikely to influence either endothelial function or low-grade systemic inflammation.ClinicalTrials.gov Identifier: NCT00696514